2021
DOI: 10.1177/1945892421998143
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MIAT Promotes Allergic Inflammation and Symptoms by Targeting MiR-10b-5p in Allergic Rhinitis Mice

Abstract: Background Allergic rhinitis (AR) is one of the most common noninfectious respiratory diseases caused by immunoglobulin E (IgE) response. Objective The study sought to explore the relationship between lncRNA MIAT and miR-10b-5p and their interaction in the regulation of allergic phenotypes in allergic rhinitis (AR) mice. Methods A mice model of AR was constructed using ovalbumin (OVA) sensitization. AR mice were treated with miR-10b-5p agomiR and LNA mediated lncRNA MIAT. The targeting relationship between MIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…Up-regulated miR-10b-5p 17, IL4, IL6, and IL17 MIAT can promote allergic inflammation and symptoms by activating the th17/ IL4/IL6 immune response via target-inhibited miR-10b-5p in AR patients [47].…”
Section: Miatmentioning
confidence: 98%
“…Up-regulated miR-10b-5p 17, IL4, IL6, and IL17 MIAT can promote allergic inflammation and symptoms by activating the th17/ IL4/IL6 immune response via target-inhibited miR-10b-5p in AR patients [47].…”
Section: Miatmentioning
confidence: 98%
“…CCND2 [814], VCAM1 [615], PDGFB (platelet derived growth factor subunit B) [795], PRKCB (protein kinase C beta) [780], ACTC1 [924], DAPK1 [947], hsa-mir-17-5p [1672], hsa-mir-2110 [1673], TCF3 [1674] and SMARCA4 [1675] are associated with developing cardiovascular diseases. CCND2 [1083], VCAM1 [761], PDGFB (platelet derived growth factor subunit B) [1059], PTCH1 [1098], FOXQ1 [1044], IGF2BP1 [1162], ACTC1 [1192], DAPK1 [947], hsa-mir-2110 [1676], hsa-mir-10b-5p [1677], TCF3 [1678], NR1I2 [1679] and TRIM28 [1680] have been shown to be associated with inflammation. Studies have shown that CCND2 [1495], VCAM1 [1462], PTPRD (protein tyrosine phosphatase receptor type D) [1496], PRKCB (protein kinase C beta) [1476], IGF2BP1 [1545], hsa-mir-200a-3p [1681] and hsa-mir-10b-5p [1682] are an important biomarkers of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al also found that lncRNA H19, LINC00895, lnc-SRGAP2C-16, lnc-HLA-C-2, lnc-APOC1-1, and lnc-B3GALT2-1 were associated with the progression of chronic non-atrophic gastritis [ 92 ]. Ma et al revealed that MIAT promoted allergic inflammation in mice with allergic rhinitis [ 93 ]. Liu et al also found that NEAT1 knockdown may attenuate LPS-induced inflammation and apoptosis in HMEECs [ 94 ].…”
Section: Discussionmentioning
confidence: 99%